Excess deaths in treatment-resistant depression. (April 2021) - Brenner, Philip; Reutfors, Johan; Nijs, Michel; Andersson, Therese M-L
Background: Patients with treatment-resistant depression (TRD) have an increased mortality risk compared with other patients with depression, but it is not known how this translates into absolute numbers of excess deaths. Methods: Swedish national registers were used to identify a cohort of 118, 774 antidepressant initiators 18–69 years old with a depression diagnosis. Patients who initiated a third consecutive treatment trial were classified as having TRD. Flexible parametric survival models were used to estimate the mortality risk due to all causes and external causes (suicides and accidents), comparing TRD patients with patients with other depression while adjusting for clinical and sociodemographic covariates and including interactions with TRD, age, and Charlson comorbidity index (CCI) for a number of somatic comorbidities. Standardized survival was estimated, as were numbers of excess deaths among TRD patients within each age and comorbidity category. Results: Compared with the mortality risk of other depressed patients, patients with TRD experienced excess deaths in most age and comorbidity categories in the range of 7–16 deaths per 1000 patients during 5 years. Highest numbers for all-cause excess deaths were found among patients 18–29 years old with CCI 1, where 16 [95% confidence interval 5–28] of the expected 37 [25–48] deaths per 1000 patients were excess deaths. The majority of the excess deaths were due to external causes. Conclusion: Patients with TRD experience significant numbers of excess deaths compared with other patients with depression.